Customary Dialogue in Oral Literature: A Comparative Study of Minangkabau Pasambahan and Kampar Malay Basiocuang in Cultural Rituals - Adib Alfalah; Evia Firnadia; Luki Aswar; Elvan Yudianda (Fakultas Ilmu Pendidikan Universitas Pahlawan Tuanku Tambusai, 2025)
This study examines Pasambahan (Minangkabau) and Basiocuang (Kampar) as two ritual oral traditions that continue to play a vital role in shaping cultural identity and social communication within their respective communities. The research is grounded in the understanding that both forms of pantun-based expression operate as living traditions whose meanings are sustained through their social and ceremonial contexts. The purpose of this study is to compare the structural, functional, and cultural dimensions of these two traditions to explain how they reflect differing systems of social organization, values, and identity. This research employs a qualitative comparative approach, integrating structural analysis, functional analysis, and cultural contextualization. Textual data, ethnographic descriptions, and ritual examples were analyzed to identify patterns in form, diction, metaphor, communicative function, and symbolic meaning. The findings demonstrate that while Pasambahan and Basiocuangshare a common four-line quatrain structure with crossed rhyme patterns, they diverge significantly in complexity, hierarchy, and communicative purpose. Pasambahan is highly hierarchical, metaphorically dense, and closely tied to Minangkabau matrilineal social structure, whereas Basiocuang is simpler, more flexible, and reflects the egalitarian and family-centered values of the Kampar Malay community. Furthermore, both traditions serve not only as ritual media but also as markers of cultural identity, embodying local cosmology, values, and social relationships. The discussion highlights that these differences are rooted in historical interactions, divergent social systems, and cultural adaptations. The study concludes that Pasambahan and Basiocuang are dynamic oral traditions whose preservation requires contextual, intergenerational, and culturally grounded strategies. Their comparative study enriches the field of oral literature and contributes to broader efforts to safeguard Indonesia’s intangible cultural heritage.